ANALISIS RISIKO PADA PRODUK BERAKAD BAGI HASIL PERBANKAN SYARIAH INDONESIA - Yohani Yohani (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2012)
This research has a purpose to analyze the deferences of risk –sharing product at indonesian islamic banking. The statistic method used to test on the research hypothesis is Independent t test. To analyzed the data using secondary data. Sample of this research consist two bank, Sharia Mandiri Banking and Muammalat Banking. Its listed at www,muamalatbank.com and www.syariah mandiri.co.id from 2002 – 2011 with times series. The result of these study with level of significance 5% uji independent t test show that (1) risk financing between of Muamalat Banking and Syariah Mandiri Banking statistically it‟snot different significantly. (2) risk of return on mudaraba financing and capital at Muamalat Banking lower than Mandiri Syariah Banking. Its mean that the risk financing for sharia product is not influenced by the history and the old age of Islamic banks, but the mudharba return on Muamalat Banking more stable so risk of return smaller.